Upaya Peningkatan Partisipasi Pendidikan Tinggi di Desa Nogosari Kecamatan Pandaan pada Masa Pandemi Covid-19 - Haikal Fahmi Harianto; Ilmiyatur Rosidah; Halimatuz Zahro; Nurul Fauziah; Suci Romadhotul Arifah (TAAWUN, 2021)
The purpose of this article is to provide knowledge and understanding to the public about the importance of education in the current situation. This activity was carried out by PGRI Wiranegara University Pasuruan in Nogosari village, Pandaan District, Pasuruan Regency during this pandemic. The program activities carried out include (1) learning assistance, (2) higher education socialization, (3) making immune-boosting herbal drinks, (4) building study houses in every hamlet in Nogosari. The method used by this program is (1) providing direct learning assistance to students who usually use the hamlet hall to study, (2) inviting students directly to study together, (3) inviting the community to be more active in supporting the education of their children. to go to school to college, (4) provide an understanding of immune-boosting herbal drinks that are useful during a pandemic. The four programs have been implemented well and have provided positive benefits and impacts for the Nogosari village community.